Enhancing Bright Band Prediction Through RadioSonde RadioWind for International Telecommunication Union-Radio Communications (ITU-R) - Banredddy, Likhitha; Maddikera, Krishna Reddy; Ravi Chandra, B; Maddikera, Lokanath Reddy; Sodum, Krishnaveni (2024 5th IEEE Global Conference for Advancement in Technology (GCAT), 2024)
As a vital source of information on atmospheric conditions at different altitudes, upper air observations are critical for precise weather forecasting, climate monitoring, and atmospheric research. In coastal areas like Vishakhapatnam that are subject to tropical cyclones and monsoonal fluctuations, radiosondes provide precise vertical profiles that are essential for weather forecasting. They also measure temperature, humidity, and pressure. The addition of wind speed and direction readings via radiowind devices, often known as "rawinsondes," improves severe weather forecasts and our understanding of atmospheric dynamics. Forecasting floods, maintaining aviation safety, and managing water resources are all aided by the ability to predict the bright band, a radar indication of the precipitation layer melting. Weather models and readiness for disasters are much improved in Vishakhapatnam when radiosondes, rawinsondes, and bright band predictions are used in tandem.